2010
DOI: 10.1007/s00280-010-1333-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of BNP7787-mediated cisplatin nephroprotection: modulation of human aminopeptidase N

Abstract: BNP7787-mediated prevention or mitigation of cisplatin-induced nephrotoxicity may involve APN inhibition by certain BNP7787-derived mesna-disulfide heteroconjugates and appears correlated to the presence of a glycinate moiety and/or an anionic group. Two general mechanisms for BNP7787-mediated nephroprotection of cisplatin-induced nephrotoxicity involving the GGT, APN and CCBL nephrotoxigenic pathway are proposed which acting in a concerted and/or synergistic manner, and thereby prevent or mitigate cisplatin-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…BNP7787 may accumulate in renal tubular cells, where it can exert its protective effects against cisplatin-induced nephrotoxicity by direct covalent conjugation of mesna with cisplatin (Hausheer et al 2011a). Besides the formation of this inactive adduct with cisplatin, other mechanisms might be involved in the protection: (a) inhibition of GGT, (b) inhibition of AP-N, and (c) inhibition of C-S lyase (Hausheer et al 2010(Hausheer et al , 2011b. Additionally, it was reported that BNP7787 does not interfere in the antitumor activity of cisplatin in human ovarian cancer cell lines in vitro or in nude mice bearing human ovarian cancer xenografts (Boven et al 2002).…”
Section: The Antitumor Mechanism Versus the Nephrotoxic Mechanismmentioning
confidence: 97%
“…BNP7787 may accumulate in renal tubular cells, where it can exert its protective effects against cisplatin-induced nephrotoxicity by direct covalent conjugation of mesna with cisplatin (Hausheer et al 2011a). Besides the formation of this inactive adduct with cisplatin, other mechanisms might be involved in the protection: (a) inhibition of GGT, (b) inhibition of AP-N, and (c) inhibition of C-S lyase (Hausheer et al 2010(Hausheer et al , 2011b. Additionally, it was reported that BNP7787 does not interfere in the antitumor activity of cisplatin in human ovarian cancer cell lines in vitro or in nude mice bearing human ovarian cancer xenografts (Boven et al 2002).…”
Section: The Antitumor Mechanism Versus the Nephrotoxic Mechanismmentioning
confidence: 97%
“…Additionally, some BNP7787-derived mesna-disulfide heteroconjugates, formed as a result of the extracellular reactions between BNP7787 and physiological thiols or between BNP7787-derived mesna and physiological disulfides, have been shown to inhibit GGT and APN. 15,16 Results of the studies herein indicate that the amount of BNP7787-derived mesna detected in lysates isolated from human HK-2 cells incubated with BNP7787 (10 mM) increased as a function of increasing incubation time. Cells generally maintain a strongly reducing intracellular environment 14,30 ; therefore, we propose that once BNP7787 enters the cell, it is likely to be reduced to the free thiol form metabolite, mesna.…”
Section: Discussionmentioning
confidence: 82%
“…In animal studies, Ormstad and Uehara 14 noted that transmembranal uptake of dimesna (BNP7787) is expected to require energy and involve an active transport mechanism; they demonstrated the uptake of BNP7787 in rat kidney perfusions and rat kidney cells. Additionally, in vitro, we have observed that BNP7787 and BNP7787-derived mesna-disulfide heteroconjugates can inhibit human γ-glutamyltranspeptidase (GGT) and aminopeptidase N (APN) enzymes 15,16 that are postulated to be important in converting cisplatin to a nephrotoxigenic species. [22][23][24][25][26][27][28][29] If there is metabolism and local action and/or local uptake of BNP7787 by renal tubular cells, it is likely that a protective mechanism exists, whereby BNP7787's disulfide bond is reduced to yield BNP7787-derived mesna, the reactive thiol (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In an additional phase III clinical trial, treatment with BNP7787 seemed to significantly improve 1-year survival of patients with advanced primary adenocarcinoma of the lung who were being treated with cisplatin and paclitaxel regimens in the first-line setting (36). Previous studies have suggested that BNP7787 seems to have significant cisplatin nephroprotective benefits (11,37,38,40,46,49,50). Based on data presented herein, we propose that BNP7787 interactions with MTP may be one mechanism through which BNP7787 may act to protect against taxane-or platinum-induced neurotoxicity by normalizing paclitaxel-induced hyperpolymerization of MTP and by forming BNP7787-derived mesna in vivo, which reacts with and inactivates the highly reactive monoaquocisplatin species.…”
Section: Discussionmentioning
confidence: 89%